Peran Bumdes Tridaya Mandiri Dalam Meningkatkan Pertumbuhan Ekonomi Desa Bhuana Jaya - Helmi (Collegium Studiosum Journal, 2018)
This study uses an empirical legal research method using a social interaction approach in order to determine the role of BUMDes Tridaya Mandiri in helping to increase economic growth in Bhuana Jaya Village, located in Tenggarong Seberang District, Kutai Kartanegara Regency, East Kalimantan Province. Sources of data used in this study use primary data sources and secondary data sources. The collection technique used in this research is observation, document study, literature study and interviews. Data analysis used qualitative analysis which presented descriptively. The description based on the results of this research is BUMDesa Tridaya Mandiri is a business entity that was established in 2017, The establishment of this business entity is due to seeing the potential for business and/or work opportunities in the village of Bhuana Jaya. BUMDes Tridaya Mandiri has work units covering, among others, an economic unit, a basic social service unit, an agricultural and livestock unit, a UMKM unit, a community empowerment unit, a socio-cultural and tourism unit, and an energy unit. The increasing economic growth of Bhuana Jaya Village is currently very pronounced where the increase in PAD generated from BUMDes Tridaya Mandiri.